Bibliometric Analysis of Current Status of Circular Economy during 2012–2021: Case of Foods - Del-Aguila-Arcentales, Shyla (2022)
“Food is usually recognized as a limited resource in sustainability, recognized by the United Nations (UN) Sustainable Development Goal (SDG) 2, which aims to achieve zero hunger. It is expected that the circular economy (CE) can improve processes related to food production. The objective of the present study was to apply a bibliometric approach using VOSviewer visualization software as a research tool to analyze the relevant literature from the Scopus database in the field of circular economy and its relation to improvements in food issues throughout 2012–2021. A total of 1316 articles were analyzed. Italy was the most productive country with 313 articles, with Wageningen University & Research the organization with the most publications with 39 articles. The top 10 institutions originated from Italy, The Netherlands, France, and Denmark. Sustainability was the most productive journal with 107 articles. Bioresource Technology had the highest average citation frequency (44.68). The study helps initiate investigations to adapt the results obtained and create new strategies for increasing food circular economy efforts“